1990
DOI: 10.1007/bf00733631
|View full text |Cite
|
Sign up to set email alerts
|

Differential exon expression in myelin basic protein transcripts during central nervous system (CNS) remyelination

Abstract: 1. In order to characterize some of the molecular events leading to repair of myelin in the adult central nervous system (CNS), we examined the expression of transcripts for myelin basic protein (MBP) during remyelination in the mouse. C57B1/6 mice develop a demyelinating disease when glial cells are selectively infected by the A59 strain of mouse coronavirus. The virus is spontaneously cleared from the mice by 4 weeks postinfection (WPI), a time when remyelination is starting. 2. At 3 WPI total MBP transcript… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

4
28
1

Year Published

1994
1994
2004
2004

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 51 publications
(33 citation statements)
references
References 35 publications
(47 reference statements)
4
28
1
Order By: Relevance
“…The expression of MBP and PLP also displayed a caudo-rostral gradient in agreement with many previous reports at both the protein and mRNA level [5,27,28,32,33], Sig nificantly, in both the spinal cord and brain, the 28 kD band of MOG appeared before the other MOG-reactive bands. If there are indeed isoforms of MOG, it could be that these different isoforms play important roles at dif ferent stages in myelin biogenesis.…”
Section: Discussionsupporting
confidence: 78%
See 1 more Smart Citation
“…The expression of MBP and PLP also displayed a caudo-rostral gradient in agreement with many previous reports at both the protein and mRNA level [5,27,28,32,33], Sig nificantly, in both the spinal cord and brain, the 28 kD band of MOG appeared before the other MOG-reactive bands. If there are indeed isoforms of MOG, it could be that these different isoforms play important roles at dif ferent stages in myelin biogenesis.…”
Section: Discussionsupporting
confidence: 78%
“…If there are indeed isoforms of MOG, it could be that these different isoforms play important roles at dif ferent stages in myelin biogenesis. This has been shown to be the case for MBP, where exon 2 containing MBP iso forms show peak expression levels early in myelination and decrease thereafter [33]. Alternatively, if the 55 kD band represents a homodimer or heterodimer, then its formation may have a critical role to play in the final stages of myelination.…”
Section: Discussionmentioning
confidence: 99%
“…Some authors (Jordan et al, 1990;Capello et al, 1997) have found that the expression of exon II-containing isoforms peaks during the initial stages of myelination and also at the onset of remyelination in mouse and human studies. The in vitro data presented in this study are consistent with our previous work in myelin isolated from aTf-injected animals (Escobar Cabrera et al, 1994).…”
Section: Discussionmentioning
confidence: 98%
“…We have induced transient, focal demyelination followed by efficient remyelination and recovery of function in C57Bl/6 mice by intracranial (i.c.) injection of murine hepatitis virus strain A-59 (MHV-A59) (Lavi et al, 1984;Woyciechowska et al, 1984;Kristensson et al, 1986;Jordan et al, 1989Jordan et al, , 1990Godfraind et al, 1989;Armstrong et al, 1990b). MHV-A59 is a coronavirus that lytically infects glial cells (Dubois-Dalcq et al, 1982), resulting in focal areas of demyelination throughout the brain and spinal cord.…”
mentioning
confidence: 98%